Prevention effect of news shocks in anti-doping policies - Maennig, W.; Schumann, V: C: E. (Journal of Sports Economics, 2022)
This paper contributes to the debate on anti-doping policies not by evaluating the policy itself but by evaluating the announcement of (new) policy measures. We develop a dynamic model for analyzing the effects of two different types of news shocks: (1) the preannouncement of improved drug testing technological opportunities and (2) the preannouncement of future increases in financial sanctions. We find that the anticipation of policy changes affects the behavior of potentially delinquent athletes. In both scenarios, our simulations show immediately reduced drug abuse among athletes. We conclude that authorities may consider news shocks as an anti-doping strategy.